(untitled) (Journal of Artificial Intelligence & Research, 2022)
Natural disasters, including hurricanes, wildfires, and earthquakes, cause catastrophic human and economic losses due to their unpredictable nature and the limitations of traditional response mechanisms. This study explores the application of artificial intelligence (AI) in enhancing disaster response systems by leveraging machine learning, data analytics, and real-time environmental monitoring. The proposed AI-driven framework integrates historical disaster data, meteorological trends, and sensor networks to predict disaster occurrences and optimize resource allocation for emergency management. Machine learning models, particularly deep learning architectures, enable precise forecasting of disaster patterns, thereby reducing response times and improving preparedness. The framework’s implementation in disaster-prone regions demonstrates its effectiveness in mitigating casualties and economic losses. The study also highlights computational challenges, data integration complexities, and the need for robust AI governance in disaster scenarios. Future advancements in AI-driven disaster response will further refine predictive capabilities and enhance adaptive mitigation strategies.